Future potential of Plaza Angsana / Julaiyha Nasir - Nasir, Julaiyha (2005)
This study is highlighting the future potential of Plaza Angsana. Plaza Angsana is one shopping complex in Johor Bahru that offer a variety of the product and services. Besides that, Plaza Angsana is located strategic placed that is closed to Johor Bahru City Center. Due to Plaza as a preference for the visitors to shopping especially from the Johorean and Singaporean people. This study has clarified four main which are to identify the factors that can to visitors at Plaza Angsana. Secondly, to the visitors satisfaction level Of Plaza Angsana. Thirdly, to identify the services quality that by Plaza Angsana. Lastly to identify the potential of Plaza Angsana to expand the business . For the purpose Of the study a set of the 100 questionnaires was distributed to the respondents that are among the visitors of Plaza Angsana. These studies have been primary and secondary data that, this study also used tie frequencies table , cross tabulation table and chi-square tested during the finding and analyzes data that have been gathered. The result of this study represents an effort of Plaza